The Curriculum in Practice and its Relationship with Learning and Knowledge Technologies (Docentes 2.0 Journal, 2021)
New cognitive ecologies mark today's society. In this sense, it is essential to lay the foundations to analyze and understand the profession of teaching within the framework of these new spaces. The present study aimed to analyze a practical case on the pedagogical use of technologies at the Higher level. The qualitative method was used for the analysis of the different data collected. From the case study, multiple sources of information were accessed, allowing the results to be corroborated, granting more excellent reliability to the findings. The results showed a series of possibilities and weaknesses when implementing the technologies; they showed different readings and interpretations by the teachers when addressing the curricular documents. Finally, the students felt more involved by working autonomously at their own pace of learning, moving towards a change in the cultural paradigm. The study allowed to deduce the reconstruction of conceptions from the teacher-directed towards a comprehensive approach to learning. Different ways of reading curricular materials evidenced multiple interpretations based on professional biographies, performance contexts, and social circumstances. On the other hand, it will be essential to tend towards a flexible curriculum, organizing teaching from diversity, with conservative approaches to different learning rates.
Keywords: Curriculum; learning and knowledge technology; teaching practice